An Integrative Fuzzy FMEA–DEMATEL Approach for Waste Reduction in Lean Implementation in Higher Education Institutions: A Literature Review: Pendekatan Integratif Fuzzy FMEA–DEMATEL untuk Pengurangan Pemborosan dalam Penerapan Lean di Institusi Pendidikan Tinggi: Tinjauan Literatur - Lusia Permata Sari Hartanti; Ivan Gunawan (PROZIMA (Productivity, Optimization and Manufacturing System Engineering), 2026)
Lean philosophy offers higher education institutions (HEIs) opportunities to improve operational efficiency. Implementing Lean Higher Education requires a systematic, structured approach, as waste in HEIs is highly complex and interrelated. This study proposes an integrative framework using fuzzy Failure Mode and Effect Analysis (FMEA) and the Decision Making Trial and Evaluation Laboratory (DEMATEL) methods to evaluate waste in HEIs. A conceptual literature review is employed to synthesize relevant articles aligned with the research objectives and to formulate an integrative fuzzy FMEA–DEMATEL framework. Fuzzy logic is used to reduce subjectivity in waste assessment, and DEMATEL is used to map causal relationships among wastes. The fuzzy FMEA-DEMATEL integration framework offers a solution for identifying and reducing waste in IPT. However, to evaluate the fuzzy FMEA-DEMATEL integration framework resulting from this study, additional empirical validation is needed.